Film Animasi 3D Sejarah Tradisi Mepasah di Desa Trunyan Bangli - Ida Bagus Putu Surya Adiwiyasa; I Gede Mahendra Darmawiguna; I Gede Bendesa Subawa (STKIP AGAMA HINDU SINGARAJA, 2023)
The 3D animation film History of the Mepasah Tradition in Trunyan Bangli Village tells about the journey of the four children in Dalem Solo who are looking for the source of the sweet smell of taru incense. On the way, the children of the king of Dalem Solo went through many obstacles and temptations so the children of the Dalem Solo had to stay. The first is Dewi Ayu Mas Meketeg living in the Batur area, the second is Ratu Sakti Sang Hyang Jero living in Kedisan village, the third is Ratu Sakti Gede Dukuh living in Abang village and the last one is, the first child of the king Dalem Solo Ratu Sakti Pancer Ring Jagat living in the Trunyan village. Ratu Sakti Pancer Ring Jagat married a goddess who guards the Tarumenyan tree, then they married and created a small kingdom. The purpose of this study is to implement a 3D animated film design for the history of the Mepasah Tradition in Trunyan Bangli Village so that people can describe the history of the Mepasah tradition. The design of the 3D animated film The History of the Mepasah Tradition in Trunyan Bangli Village uses the stages of manufacture from start to finish. The stages of making a film are divided into 3 (three) main stages, namely 1) Pre Production (Story Idea, Scriptwriting/Synopsis, Character Design, Supporting Image Design, and Storyboarding), 2) Production (Modelling, Texturing, Rigging, Skining, Animation, Lighting, and Rendering) 3) Post Production (Recording and Merging Process). The development of the 3D animated film The History of the Mepasah Tradition in Trunyan Bangli Village uses the MDLC (Multimedia Development Life Cycle) method which has 6 stages of Concept, Design, Material Collecting, Assembly, Testing, and Distribution.